Convergence of Constitutional Interpretation to the Test of Laws Through a Constitutional Dialogue Approach: Konvergensi Penafsiran Konstitusional Terhadap Pengujian Undang-Undang Melalui Pendekatan Constitutional Dialogue - Ahmad, Ahmad; Wantu, Fence M.; Ismail, Dian Ekawaty (Constitutional Court of the Republic of Indonesia, Indonesia, 2023)
The Constitutional Court's presence yields positive impacts on constitutional law, yet isn't devoid of controversies, including Judge misconduct, transgression of 'nemo judex idoneus in propria causa' principle, and potential super body transformation. This paper aims to comprehend and analyze constitutional interpretation dominance in assessing laws against the 1945 Constitution through a constitutional dialogue approach. This normative writing employs legal, historical, and conceptual methods. Findings underscore: 1) Demonstrating respect for state institutions, notably the People's Consultative Assembly of Indonesia. 2) Establishing a more democratic system to test the 1945 Constitution's compatibility in the Constitutional Court. 3) Breaking the monopoly of Constitutional Court-centric constitutional interpretation. 4) Reviving 'nemo judex idoneus in propria causa' principle is pivotal due to extensive testing of Constitutional Court Law, addressing concerns about verdict impartiality.